2020
DOI: 10.4317/medoral.23451
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric changes in alveolar ridge preservation with a compromised buccal wall: a systematic review and meta-analysis

Abstract: Background Many studies have addressed socket preservation, though fewer publications considering buccal wall loss can be found, since the literature typically considers sockets with four walls. A systematic review was made on the influence of type II buccal bone defects, according to Elian’s Classification, in socket grafting materials upon volumetric changes in width and height. Material and Methods An electronic and manual literature search was conducted in accordanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…When performing ARP in severely compromised socket, raising partial 15 or full thickness flaps 16 will be needed, such a procedure might be considered as a ridge augmentation procedure, rather than ARP. A meta‐analysis of six studies with ARP in compromised buccal wall sites, reported a high degree of heterogeneity 17 . In the current study, we focused on sites with a‐traumatic extraction with minimal soft tissues manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When performing ARP in severely compromised socket, raising partial 15 or full thickness flaps 16 will be needed, such a procedure might be considered as a ridge augmentation procedure, rather than ARP. A meta‐analysis of six studies with ARP in compromised buccal wall sites, reported a high degree of heterogeneity 17 . In the current study, we focused on sites with a‐traumatic extraction with minimal soft tissues manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of six studies with ARP in compromised buccal wall sites, reported a high degree of heterogeneity. 17 In the current study, we focused on sites with atraumatic extraction with minimal soft tissues manipulation. CMXS served as a durable barrier between the grafted socket and the oral cavity for the initial 30 days healing period.…”
Section: Discussionmentioning
confidence: 99%
“…However, the extension of alveolar bone resorption may vary depending on tooth type as observed by Couso‐Queiruga et al (2021) with a higher radiological horizontal bone resorption in molar sites vs non‐molar sites (3.61 vs. 2.54 mm). An additional bone loss of 2.4 mm in width and of 1.1 mm in height has been reported in sites with compromised buccal bone wall (García‐González et al, 2020). Interestingly, these numbers only comprise single tooth extractions, making the additional ridge resorption in cases with multiple extractions less quantifiable.…”
Section: Introductionmentioning
confidence: 95%
“…Different regenerative procedures have been proposed to neutralize alveolar resorption processes and preserve the bone for subsequent rehabilitation. Alveolar ridge preservation (ARP) using a combination of various surgical techniques and biomaterials is considered a valid therapeutic option that signi cantly reduces post-extraction ridge dimensional changes [7]. Speci cally, ARP procedures aim to minimize crestal resorption and maximize bone regeneration through the immediate placement of a biomaterial within the socket [5].…”
Section: Introductionmentioning
confidence: 99%